Tutela administrativa sin ejecución: límites y desafíos en la regulación de la solución de reclamos de usuarios ante organismos reguladores en Perú - Barco Hidalgo, Leonardo (2025)
The article analyzes the user complaint procedure in regulated sectors, highlighting its importance in the economy and the protection of consumer rights. It examines the dispute resolution function recognized for regulatory agencies, as well as the general regulatory framework applicable to Osiptel, Osinergmin, Sunass, and Sutran, in order to understand its legal-administrative nature. Based on this, key issues are discussed, such as the trilateral configuration of the procedure, the debate on whether concessionary companies can be considered part of the Public Administration when resolving complaints, and the limitations in provides a basis for reflecting on the regulatory and procedural challenges in ensuring effective protection of users’ rights in public services.